Transformation by Rous sarcoma virus: effects of src gene expression on the synthesis and phosphorylation of cellular polypeptides. - Radke, K (1979)
Infection of chicken embryo fibroblasts by Rous sarcoma virus induces a variety of alterations in cellular growth and morphology. We have used two-dimensional polyacrylamide gel electrophoresis to examine the effects of viral transformation on the pattern of synthesis and phosphorylation of cellular polypeptides. Infection by Rous sarcoma virus does not appear to induce the de novo synthesis, or the complete suppression, of any of the [35S]methionine-labeled cellular polypeptides that can be resolved with this technique; however, there are quantitative changes in a minor fraction (approximately 4%) of the [35S]methionine-labeled polypeptides. When cells labeled with [32P]orthophosphate were examined, a phosphorylated polypeptide, Mr 36,000, was detected in transformed cells; this polypeptide appears within 20 min when cells infected by a temperature-sensitive mutant of Rous sarcoma virus are shifted from the nonpermissive to the permissive temperature. Phosphorylation of the 36,000 Mr polypeptide thus represents an early event in the process of transformation, and it is possible that this polypeptide is a target for the kinase activity associated with pp60src.